Context and Virtual Communities in a Firm - Brézillon, Patrick (Computing and Informatics, 2012)
This paper revisits a case study about the consequences on the decision-making process of the introduction of IT in a newspaper firm. We consider the case study in the light of the paradigms of context, social network and virtual community. We point out that it is possible to provide a global picture of the consequence of the IT introduction in a firm and explain the dynamic of the information-management processes in such an enterprise. A first result is that making context explicit-especially shared contexts-improves notably the collaborative decision making processes in the firm. A second result is to show different interests of the simultaneous consideration of the paradigms of context, social network and virtual community.